THE EFFECT OF COMPETENCE AND TRANSFORMATIONAL LEADERSHIP STYLE ON THE MOTIVATION AND ITS IMPLICATIONS ON TEACHERS PERFORMANCE AT 01 AND 02 NORTH PETUKANGAN ELEMENTARY SCHOOL - Triadhy Wicaksono; Farida Elmi; Muhammad Havidz Aima (Dinasti International Journal of Education Management And Social Science, 2020)
The purpose of this study is to study and explain the role of competence and transformational leadership styles on the performance of 01 and 02 North Petukangan elementary school teachers, mediated by motivational variables. The research method uses quantitative and part of this research is 01 and 02 North Petukangan elementary school teachers who gathered 52 people. The sample selection is done by saturated sampling techniques or census sampling so as to make all members of the study as research samples. Data collection techniques using interviews and questionnaire instruments. Survey instruments were sent to 01 and 02 North Petukangan elementary school teachers. Data were analyzed using a structural consolidation model (SEM) with the Smart PLS software program version 3.2.8. This study revealed significant competence that were significant to teacher performance and transformational leadership style had a significant positive effect on teacher performance. Competence and leadership styles change. In addition, motivation variables do not mediate competence and transformational leadership styles on teacher performance.